Evaluation of Pharmacokinetics of Boronophenylalanine and Its Uptakes in Gastric Cancer - Tang, Futian; Wei, Yujie; Zhang, Shining; Wang, Jianrong; Gu, Wenjiao; Tang, Fenxia; Peng, Xiaohuan; Wei, Yucai; Liu, Jiangyan; Chen, Weiqiang; Zhang, Shixu; Gu, Long; et al. (Frontiers in Oncology, 2022)
Boron neutron capture therapy (BNCT), a cellular-level particle radiation therapy, combines boron compounds selectively delivered to tumor tissue with neutron irradiation. Boronophenylalanine (BPA) is a boron compound widely used in malignant melanoma, malignant brain tumors, and recurrent head and neck cancer. However, neither basic nor clinical research was reported for the treatment of gastric cancer using BPA. Selective distribution of boron in tumors rather than that in blood or normal tissue prior to neutron irradiation is required for the successful treatment of BNCT. This study evaluated the pharmacokinetics and safety of 10B-labeled BPA (10B-BPA, abbreviated as BPA) and its uptakes in gastric cancer. Pharmacokinetics and safety were evaluated in Sprague–Dawley (SD) rats intravenously injected with BPA. The uptakes of boron in gastric cancer cell line MKN45 and in cell-derived xenografts (CDX) and patient-derived xenografts (PDX) animal models were measured. The results showed that the boron concentration in the blood of rats decreased fast in the first 30 min followed by a steady decrease following the observation time, having a half-life of 44.11 ± 8.90 min and an AUC-last of 815.05 ± 62.09 min×μg/ml. The distribution of boron in different tissues (heart, liver, lung, stomach, and small intestine) of rats revealed a similar pattern in blood except for that in the brain, kidney, and bladder. In MKN45 cells, boron concentration increased in a time- and concentration-dependent manner. In both CDX and PDX animal models, the boron is preferentially distributed in tumor tissue rather than in blood or normal tissues. In addition, BPA had no significant adverse effects in rats. Taken together, the results suggested that BPA revealed a fast decrease in boron concentration in rats and is more likely to distribute in tumor cells and tissue.